Contextualizing corrective feedback in scientific writing through online learning platforms - Saragih, Erikson; Zein, T Thyrhaya; Sumbayak, Desri Maria (Universitas Syiah Kuala, 2023)
Providing corrective feedback by teachers is one of the most crucial and central activities to improve the quality of student scientific writing. Although there has been much previous research on corrective feedback, few focused on lecturers' viewpoints, techniques, and assessments to guide students to write scientific papers. The objectives of this study are to describe lecturers' perceptions, practices, and self-evaluation when providing written corrective feedback in the context of scientific writing in the field of English research at multiple Indonesian teacher education institutes. The researchers employed a qualitative descriptive research method with a survey design to meet research objectives. A total of 53 lecturers were selected as respondents using purposive sampling criteria. This study used a survey questionnaire with ten questions of three categories (perception, activity, and evaluations) which were distributed to the research participants. The results of this study revealed that teachers prefer written corrective feedback, use various media and applications, emphasize the content of writing in providing feedback, and feel confident in doing this activity, even though sometimes they do not have enough time and continue to try to improve the quality of feedback provision to their students in writing scientific works. The results of this study can contribute as a reflection to improve teacher performance in the implementation of corrective feedback, especially in an online learning platform.